On the exposure of insurance companies to sovereign risk: Portfolio investments and market forces - Robert Düll; Felix König; Jana Ohls (Deutsche Bundesbank, 2015)
A sovereign debt crisis can have significant knock-on effects in the financial markets and put financial stability at risk. This paper focuses on the transmission of sovereign risk to insurance companies as some of the largest institutional investors in the sovereign bond market. We use a firm level panel dataset that covers large insurance companies, banks and non-financial firms from nine countries in the time period January 1st 2008 to May 1st 2013. We find significant and robust transmission effects from sovereign risk to domestic insurers. The impact on insurers is larger than for non-financial firms and slightly smaller than for banks. We find that systemically important insurers were more closely linked to the domestic sovereign. Based on European data, we show that risks in sovereign bond portfolios are an important driver of insurer risk, which is not reflected in current insurance regulation (incl. upcoming Solvency II in Europe).
Keywords: G22; G28; G15; 330; insurance; sovereign risk; sovereign bond portfolio